Internationalization of Japanese Universities: Learning from the CAMPUS Asia Experience - Horie, Miki (International Higher Education, 2014)
This article focuses on the policy development and program implementation of CAMPUS Asia, a policy jointly initiated by the governments of Japan, China, and Korea. It illustrates that internationalization efforts bring opportunities for university practitioners to apply non-traditional types of teaching and learning in Japan, such as experiential, active, and collaborative learning models. The program implementation is a learning process for students as well as teaching and administrating staff. The ‘East Asia Leaders’ program identifies the following indicators for the further development and implementation of meaningful multicultural joint programs: (1) the quality in teaching and coordinating staff in terms of pedagogical understandings, (2) the development of outcome measurement schemes for intercultural learning in the East Asian context, and (3) the examination of differences in pre-knowledge and social/personal expectations of students.